Approach for sintering nano-sized yttria-stabilised zirconia. (17th July 2007) - Hasanuzzaman, M.; Rafferty, A.; Olabi, A.G.; Prescott, T.
Commercially available nano-sized ZrO2-3mol%Y2O3 (TZ-3Y-EB.) was investigated. Particle size of powder was found to be 1.29 ?m, suggesting that the particles agglomerate in water. BET analysis yielded a specific surface area of 14.52 m?/g. The powder had a true density of 5.98 g/cm? when analysed using helium gas pycnometry. DTA/TGA analysis indicated that binder burnout occurred on heating in the range 300-400?C. An expansion associated with the tetragonal to monoclinic transformation on cooling from 1400?C was observed by dilatometry for unstabilised zirconia but not for TZ-3Y-EB. The density of discs which were sintered across the temperature range 1350?C to 1500?C varied between 6.02 g/cm? and 6.05 g/cm?, corresponding to 99.12% and 99.49% of theoretical density. Dilatometry showed that a maximum shrinkage rate occurred at 1285?C. X-ray diffraction data revealed that the starting TZ-3Y-EB powder contained some monoclinic zirconia, but that discs sintered from this powder were wholly tetragonal after sintering.